Analisis Kepemimpinan Transformasional Membangun Inovatif Capabillity dalam Meningkatkan Kinerja Sumber Daya Manusia pada Perguruan Tinggi Swasta Kota Jawa Tengah. - Teti Safari; Ihda Nor Rohmah (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to develop a leadership theory that builds innovative capability for organizations in the modern era. Innovative Capability is a mechanism that underlies the effect of transformational leadership on creativity. This Innovative Capability aims to improve the performance of human resources of lecturers working in the education industry such as lecturers. This study involved 100 human resources of lecturers. Data were collected using a questionnaire and analyzed using Smart PLS analysis. The results of the study indicate that there is a significant positive influence between Transformational leadership on the Performance of Human Resources of Lecturers and individual performance. In addition, Innovative Capability has also been shown to moderate the relationship between Transformational leadership and the performance of Human Resources of Lecturers. The implication is that transformational leadership will be proven to improve the performance of lecturer HR, if organizational leaders are able to build lecturer innovation capabilities.